Influence of Some Biostimulants and Seaweed Extracts on Growth and Fruit Characteristics of Strawberry (Fragaria x ananassa Duch.) - Taha, Shler M.; Haji, Ghazi Faiq (Sulaimani Journal for Pure and Applied Sciences, 2015)
This study was conducted during (2013 -2014) season at Girda-Rash field, College of Agriculture, University of Salahaddin, Erbil governorate, Iraqi Kurdistan Region to study the effect of biostimulants as microbial inoculants (Fulzyme SP and Fulzyme Plus SP) and seaweed extracts as seamino on some vegetative growth and fruit characteristics of two short day cultivars of Strawberry ‘Rubygem’ and ‘Florida Fortuna’, the experimental units were arranged in split plot in a randomized complete block design with four replicates. The obtained results indicated that the ‘Rubygem’ cultivar was superior in the characteristics of leaf area and shoot dry weight, while no significant difference was obtained between the two cultivars in total chlorophyll content and root dry weight. On other hand ‘Rubygem’ cultivar recorded highest significant value in number of fruits per plant, fruit fresh weight and plant yield, however no significant difference was found between the two cultivars in fruit size. Fulzyme Plus SP application caused significant increase in the leaf area, total chlorophyll content, shoot dry weight and root dry weight, also application of Fulzyme Plus SP significantly increased the number of fruits per plant, fruit fresh weight, fruit size and plant yield, and the highest value in plant yield was recorded as a result of interaction effects of Rubygem x Fulzyme Plus SP.
Keywords: Strawberry; Biostamulants; Seaweed extracts; Vegetative growth; Fruit characteristics